Insulin resistance and metabolic syndrome in generalized anxiety disorder: a cross-sectional study - Kalva, L. Tejaswini; Jannabhatla, V. B. Kasyapa; Anusha, Nageli; Tirupathe, Sunanda (International Journal of Research in Medical Sciences, 2024)
Background: Generalized anxiety disorder (GAD) involves persistent and excessive anxiety affecting daily activities for at least six months, often accompanied by restlessness, fatigue, irritability, muscle tension, and sleep difficulties. Insulin resistance (IR) and metabolic syndrome (MetS) are linked to psychiatric disorders due to their impact on the central nervous system. This study aims to assess IR and MetS prevalence in GAD patients and explore their relationship with GAD severity. Methods: In a six-month cross-sectional study at a tertiary care center in southern India, 66 patients aged 18-60 diagnosed with GAD per DSM-5 criteria were included. Exclusion criteria were other psychiatric disorders, significant medical conditions, and specific medication use. GAD severity was assessed using the Hamilton anxiety rating scale (HAM-A). IR was calculated using the homeostatic model assessment of insulin resistance (HOMA-IR) formula, with a value of 2.5 or higher indicating significant IR. MetS was diagnosed based on the International Diabetes Federation's criteria. Results: Among the 66 participants (59.1% female, mean age 43.41 years), 39.4% had severe GAD. Significant IR was present in 39.4% of participants, while 34.8% met the criteria for MetS. No significant correlation was found between GAD severity and IR or MetS, although a sedentary lifestyle was notably higher in GAD patients (57.6%). Conclusions: The study highlights a high prevalence of IR and MetS among GAD patients, without a significant correlation with GAD severity. Routine metabolic screening and integrated management strategies are recommended for GAD patients to address both mental and metabolic health concerns.